Differential and additive effects of natural biotic and anthropogenic noise on call properties of Odontophrynus americanus (Anura, Odontophryinidae): Implications for the conservation of anurans inhabiting noisy environments - Grenat, Pablo Raúl (2019)
Successful reproduction in most anurans is associated to acoustic communication and negative effects of auditory masking by natural biotic and anthropogenic noise are known in this group. However, the potential additive effect of both noise types has been scarcely studied. We examine in situ the acoustic variation of 135 males (n = 975 calls) of Odontophrynus americanus in areas from Central Argentina with (TN) and without traffic noise (N-TN) and in presence (Ch) or absence (N-Ch) of chorus. The effect of noise condition on four call properties (call duration [CD], intercall interval [ICI], pulse rate [PR] and dominant frequency [DF]) were analyzed using linear mixed models (LMM and GLMM). A Principal Component Analysis (PCA) was performed to identify the acoustical properties that best accounted for variation among all possible noise conditions (N-TN/N-Ch; N-TN/Ch; TN/N-Ch and TN/Ch). PR and DF showed significant higher values in TN than N-TN sites while a significant increase in ICI and a decrease in DF were found in chorus situation. Analyzing combined effects, PR significantly increased in N-TN/N-Ch condition and decreased under TN/Ch. ICI was significantly higher in N-TN/N-Ch condition. PCA showed a separation of males calling in noisy condition mainly associated to higher values of DF and CD. The acoustic variation observed in noisy environments could have implications in the reproductive strategies of the individuals although new studies should be conducted to analyze the effect of this variation on the recognition and choice by females. Our outcomes highlight the importance of conducting in situ behavioral studies considering the additive effects of different environmental noise sources.